2020
DOI: 10.1038/s41467-020-15330-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of nucleic acids using deformed graphene channel field effect biosensors

Abstract: Field-effect transistor (FET)-based biosensors allow label-free detection of biomolecules by measuring their intrinsic charges. The detection limit of these sensors is determined by the Debye screening of the charges from counter ions in solutions. Here, we use FETs with a deformed monolayer graphene channel for the detection of nucleic acids. These devices with even millimeter scale channels show an ultra-high sensitivity detection in buffer and human serum sample down to 600 zM and 20 aM, respectively, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
286
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(293 citation statements)
references
References 67 publications
5
286
0
2
Order By: Relevance
“…However, it was found that the solution commonly used to store respiratory virus samples, the universal transport medium (UTM), can produce a high noise signal and thus, the LOD in UTM decreased to 242 copies/mL ( Seo et al, 2020 ). Novel materials or engineering methods must be developed to reduce noise signals in FET biosensors, and thereby improving the signal-to-noise ratio to allow high sensitivity screening of low virus load COVID-19 patients ( Hwang et al, 2020 ). Moreover, coupling FET sensors with magnetic particle pre-concentration before detection can minimise the effect of interferents on sample matrix by attracting immunocomplex onto the surface of the sensor via an external magnetic field, thereby increasing detection sensitivity and producing a high signal-noise ratio ( Farka et al, 2017 ).…”
Section: Sars-cov-2 Virus Particle Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was found that the solution commonly used to store respiratory virus samples, the universal transport medium (UTM), can produce a high noise signal and thus, the LOD in UTM decreased to 242 copies/mL ( Seo et al, 2020 ). Novel materials or engineering methods must be developed to reduce noise signals in FET biosensors, and thereby improving the signal-to-noise ratio to allow high sensitivity screening of low virus load COVID-19 patients ( Hwang et al, 2020 ). Moreover, coupling FET sensors with magnetic particle pre-concentration before detection can minimise the effect of interferents on sample matrix by attracting immunocomplex onto the surface of the sensor via an external magnetic field, thereby increasing detection sensitivity and producing a high signal-noise ratio ( Farka et al, 2017 ).…”
Section: Sars-cov-2 Virus Particle Detectionmentioning
confidence: 99%
“…By virtue of this modified sensor, as few as 60 chondroitin sulfate proteoglycan 4 (0.01 fM) molecules could be detected in undiluted serum ( Yeh et al, 2016 ). A recent study adopted crumpled graphene to increase the Debye length (e.g., shielding of the molecule charge by the counter ions in the solution); thereby enhancing the detection sensitivity of the graphene FET ( Hwang et al, 2020 ). The further combination of the high DNA binding capacity of PNAs and the crumpled graphene FET showed ultra-high sensitivity nucleic acid detection in buffer and human serum samples, with LOD down to 600 zM and 20 aM, respectively, in a 1-h incubation time; these LODs are significantly lower than those of the flat, reduced graphene oxide FET biosensors ( Cai et al, 2014 ; Hwang et al, 2020 ).…”
Section: Potential Biosensors For Point-of-care Sars-cov-2 Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The films are prone to the introduction of cracks and wrinkles, which lead to a deterioration of the physical properties [55]. In contrast, a systematic introduction of defects by transferring cvdG, specifically to form a wrinkled layer, was found to induce a bandgap [56]. Besides the transfer, also a modification might induce defects within the CVD grown layer.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…Potentially every single atom of the structure can be affected by an adsorbate, making graphene's inherent sensitivity high. Graphene based field-effect-transistor (GFET) sensor is a common and reliable sensor [204], and has been used recently e.g., for early detection of the Zika-virus [205], RNA and DNA detection down to 10 -17 mol/L concentrations [206,207], in operando TEM measurements of neuropeptide capture and release [208] as well as detection of SARS-CoV-2 virus [209], the cause of the global COVID-19 pandemic of 2020. Other measurement schemes can be used as well, such as, Hall effect in standard [210], gated [211] and photonic spin [212,213] Table 2 Summary of different graphene based transparent electrodes, where R s , T, DC / OP and R change refer to sheet resistance, transmittance (at nm unless otherwise specified), figure of merit and decrease of sheet resistance due to doping, respectively.…”
Section: Applicationsmentioning
confidence: 99%